Phenolic compounds seasonal occurrence and risk assessment in surface and treated waters in Minas Gerais—Brazil - Ramos, Ramatisa L.; Moreira, Victor R.; Lebron, Yuri A.R.; Santos, Amanda V.; Santos, Lucilaine V.S.; Amaral, Míriam C.S. (Environmental pollution (1987), 2021)
This study provided a monitoring of phenolic compounds occurrence in a river and in its treated water by a conventional water treatment plant (WTP) throughout a year-period, in Minas Gerais - Brazil. Furthermore, the environmental risk (hazard quotient - HQ), the human health risk (margin of exposure - MOE), and the cancer risk were calculated for the compounds. The results indicated that sixteen out of the seventeen investigated phenolic compounds were detected at some point during the sampling campaign. The most frequent compounds in the raw surface water were 2,3,4–trichlorophenol (234TCP), 2,4–dimethylphenol (24DMP), and 4–nitrophenol (4NP), whereas in treated water were 4NP and bisphenol A (BPA). In addition, the highest total concentration values were corelated to the months in which there was less precipitation, demonstrating that the presence of this micropollutants may be subject to seasonality. From the treated water results, it was not possible to state the efficiency of the conventional WTP in eliminating the phenols, since in some samples the phenolic compounds were totally removed and in others their increase or formation occurred. Regarding to the risk assessments, most of the evaluated compounds were considered highly toxic to some trophic level and posed a significant human health risk. Additionally, the risk reduction of phenolics using conventional WTP was low. The sixteen phenols contamination in surface and drinking waters appears to be subject to seasonality. Besides that, an alarming risk for environment and human health was identified. [Display omitted] •Seventeen phenolic compounds were monitored in raw and treated water for one-year.•Treated water physicochemical properties attained the standard recommendations.•The micropollutants presence in the raw water appears to be subject to seasonality.•The phenols removal by the water treatment plant varied from 50.0 to >99.9%.•Twelve compounds presented a high risk even after conventional treatment.